BUSINESS PLAN AS AN INDICATOR OF THE CURRENT SITUATION AND FUTURE PERSPECTIVES OF COMPANIES BUSINESS ACTIVITIES - Stankov, Biljana M; Stojaković, Aleksandra; Vapa Tankosić, Jelena (International Journal of Economic Practice and Policy, 2016)
Business planning and business plan construction are very important segments of strategic management. Whether it is made for the needs of internal users or serve as a means of presenting business ideas and important operational, technical, market and financial information to external users, business plan certainly has a key role in the enterprise management. Entrepreneur as a potential source of financing will often start to establish communication through the business plan. The purpose of the paper is to inform and to consider the point of view of many authors on the concept, role and importance of a business plan, as well as the specifics of the key factors in the process of its development. The aim is to highlight the more formal and less substantive difference between the methodologies of a business plan making which are applied by renowned international and national institutions or proposd by some authors. The fact that for about 80% of potential investors submission of a business plan is the first step when considering the idea of ​​investing funds in a specific business venture points to the imrtance of this topic. Whether the potential investor will just browse or will thorougly consider the submitted business plan depends primarily on the business plan quality.